Keuntungan Usaha Kerupuk Fajar di Desa Kalasey Satu Kecamatan Mandolang - Raden Ayu Sartika; Jean Fanny Junita Timban; Oktavianus Porajouw (AGRI-SOSIOEKONOMI, 2023)
The purpose of this study was to analyze the profits of the Fajar Crackers business in Kalasey Satu Village, Mandolang District. This research was carried out for 3 months from October to December 2022. The sampling method used the method purposive sampling. The research uses primary data obtained from direct interviews with Mr. Catur Pujiono who is the owner of the Fajar Crackers business. Secondary data were obtained from the literature and previous studies related to this research. The analytical method used in this study is descriptive analysis and then analyzed using profit analysis. The results showed that in one month, the Fajar Crackers Business earned a profit of IDR5.420.927.